Analisis Kandungan Sisa Chlor Pada Jaringan Distribusi PT. Water Treatment Plant 1 Jababeka Infrastruktur Dengan Menggunakan Simulasi Software Epanet 2.0 - Safrizal Rachmana Putra; Dodit Ardiatma; Nur Ilman Ilyas (Prosiding Sains dan Teknologi, 2022)
Water is a natural resource that has very high economic value, especially when viewed from a biological and cultural point of view. The purpose of this final project is to compare the simulation results of the Epanet software to the residual chlorine content in the distribution network of Water Treatment Plant 1 Jababeka. Lack of supervision and sampling of residual chlorine at a certain point, Comparing residual chlorine levels from measurements in the field with Epanet software. Analyzing the relationship of residual chlorine to distance in the distribution network of Water Treatment Plant 1 Jababeka Infrastructure. Drinking Water Disinfection is an inactivation method (kills pathogenic microorganisms found in drinking water. This disinfection method aims to kill disease-causing microorganisms (pathogens), either from processing installations or entering through distribution networks. These microorganisms can be in the form of viruses (causes poliomyelitis). ), bacteria (the cause of cholera, dysentery, typhoid fever and so on), and other microorganisms. The results of the residual chlorine measurement provide information that there is a decrease in residual chlorine levels at each sampling point. The residual chlorine at the sampling location based on measurements in the field generally has met the standard criteria are 0.2 mg/L - 1 mg/L. The minimum average residual chlorine content is 0.53 mg/L and the maximum is 0.85 mg/L in the distribution network. The results of field measurements show that residual chlorine is in the range 0.48 mg/L to 0.87 mg/L. Based on the measurement results using Epanet software, the residual chlorine ranges from 0.4 8 mg/L to 1 mg/L. the farther the distance of the water, the less the residual chlorine content, with the furthest distance of 2,616 m of residual chlorine obtained is 0.48 mg/L Keywords : Epanet , Disinfection , Residual Chlorine